Celiac disease and functional abdominal pain disorders: Are they the same? A literature review - Ana C. Falcon (Permanyer, 2021)
Approximately one in three children complain of abdominal pain weekly; between 3 and 7% of all children with abdominal pain are referred to gastroenterologists. Celiac disease (CD), a common immune-mediated inflammatory disease of the small intestine is usually suspected; while functional abdominal pain disorders (FAPDs) characterized by an abnormally elevated sensibility to pain, is the cause of more than half of all consultations. CD can mimic FAPDs, making both conditions difficult to distinguish clinically. A potential overlap of FAPDs and CD constitutes another conflict for the long-term treatment of patients with either or both diagnoses. This literature review has the objective to educate on how to distinguish both conditions, considering they have different management, treatment and consequences on the patient's quality of life. Early differentiation and diagnosis will prove to be beneficial to the patient itself and their families that tend to be subject to prolonged testing.